RANBP1, a member of the nuclear-cytoplasmic trafficking-regulator complex, is the terminal-striking point of the SGK1-dependent Th17+ pathological differentiation - Brescia, Carolina; Dattilo, Vincenzo; D’Antona, Lucia; Chiarella, Emanuela; Tallerico, Rossana; Audia, Salvatore; Rocca, Valentina; Iuliano, Rodolfo; Trapasso, Francesco; Perrotti, Nicola; Amato, Rosario (Frontiers in Immunology, 2023)
The Th17 + arrangement is critical for orchestrating the innate and acquired immune response. In this context, the serum and glucocorticoid regulated kinase 1 (SGK1) exerts a key role in the governance of IL-23R-dependent Th17 + maturation, through the phosphorylation-dependent control of FOXO1 localization. Our previous work has shown that some of the SGK1-key functions are dependent on RAN-binding protein 1 (RANBP1), a terminal gene in the nuclear transport regulation. Here, we show that RANBP1, similarly similar similarly to SGK1, is modulated during Th17 + differentiation and that RANBP1 fluctuations mediate the SGK1-dependent effects on Th17 + maturation. RANBP1, as the final effector of the SGK1 pathway, affects FOXO1 transport from the nucleus to the cytoplasm, thus ha formattato: Apice ha formattato: Non Apice / Pedice ha formattato: Tipo di carattere: Grassetto 2 This is a provisional file, not the final typeset article enabling RORγt activation. In this light, RANBP1 represents the missing piece, in an essential and rate-limiting manner, underlying the Th17 + immune asset.